Characterization of chemokine and cytokine expression pattern in tuberculous lymphadenitis patient - Novita, Bernadette Dian; Tjahjono, Yudy; Wijaya, Sumi; Theodora, Imelda; Erwin, Ferdinand; Halim, Stefan Wilson; Hendrawan, Bobby; Jaya, David Karunia; Tahalele, Paul L. (Frontiers in Immunology, 2022)
Introduction C-C chemokine receptor-2 (CCR-2) and C-C chemokine ligand-5 (CCL-5) play an important role in the migration of monocytes, macrophages, dendritic cells, and activated T cells against Mycobacterium tuberculosis (M.tb). Meanwhile, signal transducer and activator of transcription 3 (STAT-3) and suppressor of cytokine signaling 3 (SOCS-3), activated by interleukin (IL)-6 and IL-10 in tuberculosis (TB) infection, play an important role in phagocytosis, inflammation, and granulomatous-forming processes that may lead to TB treatment success or failure. However, there are no data about the expression of those markers in tuberculous lymphadenitis. The characterization of those markers is very critical to put a fundamental basis to understand the homing mechanism of tuberculous lymphadenitis. Aim of study The specific objective of this study is to characterize the expression pattern of CCR-2-CCL-5, IL-6, IL-10, STAT-3, and SOCS-3 in tuberculous lymphadenitis. Methods The study was performed on 27 cases of tuberculous lymphadenitis node biopsies. The diagnosis of tuberculous lymphadenitis was based on the clinical criteria and the presence of the histological feature characteristic of TB granulomas. Afterward, immunohistochemistry was stained with CCR-2, CCL-5, IL-6, IL-10, STAT-3, and SOCS-3. A semiquantitative analysis of IHC images was performed to examine protein expression in stained preparations. The expression was also manually counted. Results Compared with the normal area, both lymphocytes and macrophages expressed strongly CCR-2-, CCL-5, and IL-6, while IL-10, STAT-3-, and SOCS-3- were expressed lowly. There was a strong positive correlation between CCR-2 with IL-6 (p = 0,83) and IL-10 (p = 0,83). Conclusion The chronic infection process of tuberculous lymphadenitis was characterized by the expression of IL-10low, STAT-3low, SOCS-3low, CCR-2high, CCL-5high, and IL-6high. Clinical Trial Registration Clinicaltrials.gov, identifier NCT05202548.